Retrospective detection and sequencing of Canine Distemper Virus in road-killed Eurasian otter (Lutra lutra) samples from the last two decades. (March 2022) - Lanszki, Z.; Lanszki, J.; Toth, G.; Jakab, F.; Kemenesi, G.
Abstract : Purpose: Canine distemper virus (CDV) is a single-stranded negative-sense RNA virus, which belongs to the Paramyxoviridae family in the Morbillivirus genus. Based on nucleotide sequence analysis of the hemagglutinin (H) gene several distinct genotypes are known in different hosts and geographical areas worldwide. A wide range of domestic animals and wild carnivores are at risk. The Eurasian otter ( Lutra lutra ) is a piscivorous top predator of aquatic habitats. Although, the otter is a widely distributed and well-studied, flagship species in Europe, there is a considerable lack of knowledge in virological context. The understanding of CDV epidemiology in Eurasian otter is of great importance for veterinary health and nature conservation point of view. Therefore, our aim was to perform a retrospective study, spanning a ∼20 years time period to reveal the set of CDV genotypes in connection to Eurasian otter infections. Methods & Materials: Altogether 329 lung tissue samples of otters collected in Hungary between 2002 and 2021were examined. All samples are derived from road-killed animals, therefore we do not have the data of existing symptoms at the time of death. The samples were RT-PCR screened for Canine Distemper Virus. The positive samples were sequenced with a pan-genotype CDV-specific amplicon-based sequencing method developed by our research group for Oxford Nanopore Technologies platform.. The detailed protocol is available at our laboratory protocol.io page. Results: Two animals out of the 329 were positive for CDV RNA. One positive sample is from 2006 and the other is from 2010. In one case, complete genome sequencing was performed with a MinION nanopore sequencing, Oxford Nanopore technology. In the other case, the virus titer was too low to subject for complete genome sequencing. We applied additional PCR, targeting the hemagglutinin (H) gene of CDV and sequenced on regular Sanger Sequencer platform. Conclusion: In addition to the description and characterization of CDV relatively little information is available on the ecological background of the virus, or even their effects on otter populations. We present the importance of CDV infections in managing stable Eurasian otter populations and highlight the reliability of road-killed animals for virological studies.